Hif-3α Fine-tunes Extracellular Matrix Production in Nucleus Pulposus Cell under Hypoxia. Issue 1 (April 2016) - Tam, Wai-Kit; Cheung, Kenneth M. C.; Leung, Victor Y. L.
Introduction: Nucleus pulposus (NP), the gelatinous tissue core in the intervertebral disc (IVD), is enriched with extracellular matrix type II collagen (encoded by COL2A1 ) and aggrecan (encoded by AGC1 ). Dysregulation of extracellular matrix proteins in the NP is tightly associated with disc degeneration, ultimately leading to a loss of mechanical function in motion segments. 1 Expression of SOX9, the major chondrogenic transcription factor for COL2A1 and AGC1 gene activation, was evidenced in the normal and degenerated human NP, but weak in the annulus fibrosus (AF) region. 2 Considering the virtually avascular characteristic of the NP, NP cells are regulated within a hypoxic microenvironment. Among the family of hypoxia inducible factor-α subunits (HIF-α), HIF-1α and HIF-2α (EPAS1) have been well illustrated as important transcription factors in maintaining disc cell and matrix homeostasis, particularly in the NP. 3–5 However, the understanding of HIF-3α, the dominant negative regulator of HIF-1α, 6 in IVD is limited. Here, we hypothesized that HIF-3α may regulate the SOX9-dependent transcription of the extracellular matrix genes in NP cells under hypoxia. We aimed at characterizing the sub-cellular expression patterns of HIF-1α and HIF-3α in mouse IVD tissues and human NP cells cultured under different oxygen tensions. Moreover, we tested the modulatory effects of HIF-1α/HIF-3α on the expression of Col2a1 and Agc1 using Sox9-expressing mouse prechondrocytic cells as a model. Materials and Methods: All animal and human works were approved by local ethical committee. IVD were harvested from wild-type C57BL/6N mice at 3 and 6 months-old. Lumbar IVD of scoliosis patients were collected under informed consent. Cells were harvested by digestion with 0.5 × of TrpLE Express ( Gibco ) 37°C, 30 minute and 0.25mg/ml Collagenase II ( Gibco ) 37°C, 90 minute in DMEM-HG ( Gibco ). Human NP cells were expanded in DMEM-HG supplemented with 10% fetal bovine serum. Subsequently, human NP cells were subjected to ambient oxygen tension (21% O2 ) or intermediate hypoxia (5% O2 ) or extreme hypoxia (1% O2 ) for 72 hours prior to fixation or RNA collection. Immunohistochemistry staining of Hif-1α and Hif-3α was studied with mouse IVD paraffin sections and different sub-cellular locations of HIF-1α, HIF-3α and SOX9 expression were identified by immunofluorescence in human NP cells cultured under different oxygen tensions. To determine transcriptional activity of Col2a1 and Agc1, luciferase-based promoter assays on specific Col2a1 or Agc1 cis -acting elements with the overexpression for each of the HIF-α subunits and/or Sox9 in ATDC5 cells were performed. Results: Hif-1α and Hif-3α expression pattern was identified in mouse NP, AF and endplate (EP) tissue. Expression of HIF-1α and SOX9 was detected in the nuclei of human NP cells independent of different oxygen tensions. Strikingly, induction of HIF-3α expression in nuclei was observed in human NP cells cultured under hypoxia (5% and 1% O2 ) versus normoxia (21% O2 ). Additionally, AGC1 gene expression was reduced in human NP cells cultured under hypoxia in comparison with normoxia. Furthermore, luciferase-based promoter assay showed that Hif-3α overexpression inhibited the Sox9–dependent transcriptional up-regulation of Col2a1 and Agc1 . Conclusion: Our findings illustrated that induction of HIF-3α in human NP cell nuclei was evidenced in hypoxia versus normoxia. We further demonstrated that Hif-3α has a function in inhibiting Sox9-mediated transcriptional regulation of Col2a1 and Agc1 in prechondrocytic cells, implicating a possible role of HIF-3α in fine-tuning the extracellular matrix protein production in NP cells under hypoxia. Detailed molecular mechanism of HIF-3α in regulating human NP cell and matrix homeostasis under hypoxia warrants further investigations. References Richardson SM, Hoyland JA, Mobasheri R, Csaki C, Shakibaei M, Mobasheri A. Mesenchymal stem cells in regenerative medicine: opportunities and challenges for articular cartilage and intervertebral disc tissue engineering. J Cell Physiol 2010;222(1):23–32 Sive JI, Baird P, Jeziorsk M, Watkins A, Hoyland JA, Freemont AJ. Expression of chondrocyte markers by cells of normal and degenerate intervertebral discs. Mol Pathol 2002;55(2):91–97 Rajpurohit R, Risbud MV, Ducheyne P, Vresilovic EJ, Shapiro IM. Phenotypic characteristics of the nucleus pulposus: expression of hypoxia inducing factor-1, glucose transporter-1 and MMP-2. Cell Tissue Res 2002;308(3):401–407 Risbud MV, Guttapalli A, Stokes DG, et al. Nucleus pulposus cells express HIF-1 alpha under normoxic culture conditions: a metabolic adaptation to the intervertebral disc microenvironment. J Cell Biochem 2006;98(1):152–159 Agrawal A, Gajghate S, Smith H, et al. Cited2 modulates hypoxia-inducible factor-dependent expression of vascular endothelial growth factor in nucleus pulposus cells of the rat intervertebral disc. Arthritis Rheum 2008;58(12):3798–3808 Dengler VL, Galbraith MD, Espinosa JM. Transcriptional regulation by hypoxia inducible factors. Crit Rev Biochem Mol Biol 2014;49(1):1–15